INTERFERENCE IN THE SHORT TEXT OF BESAKIH TEMPLE - Ni Made Kajeng Martha Puspita (Lingual: Journal of Language and Culture, 2016)
The aim of this study is to analyze the four types of interferences; syntax, semantics, copula,and redundant found in “Besakih Temple” short text. The data were collected through libraryresearch with the necessary note-taking and documentation. The method used in analyzingthis study is qualitative method. The result showed that interferences found in the text arecovering linguistic aspects. It is furthermore called the negative transfer due to the result ofcontact with another language. The most common source of errors is lack of knowledge ofthe speaker about the language being used.